Stochastic detection and characterisation of individual ferrocene derivative tagged graphene nanoplatelets. Issue 9 (2nd February 2016) - Wu, Haoyu; Lin, Qianqi; Batchelor-McAuley, Christopher; Gonçalves, Luís Moreira; Lima, Carlos F. R. A. C.; Compton, Richard G.
Abstract : Graphene nanoplatelets (GNPs) are 'tagged' with 1-(biphen-4-yl)ferrocene, which has been studied via nano-impacts to derive the corresponding surface coverage. Abstract : Graphene nanoplatelets (GNPs) are 'tagged' with 1-(biphen-4-yl)ferrocene. Chronoamperometry is then utilised to observe single particle impacts when GNPs suspended in solution collide with a carbon fibre micro wire electrode held at an oxidising potential, resulting in current/time transient "spikes". The impacts are associated with two types of charge transfer: Faradaic due to oxidation of the 'tag' and capacitative due to disruption of the double layer. Analysis of the spikes suggests approximate monolayer coverage of 1-(biphen-4-yl)ferrocene on the GNP surfaces, with a surface coverage of (2.2 ± 0.3) × 10 −10 mol cm −2 . In contrast non-derivatised ferrocene does not exhibit any significant adsorption on the GNP material.